2011
DOI: 10.1371/journal.pone.0020611
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metaproteomic Analysis on Consecutively Rehmannia glutinosa-Monocultured Rhizosphere Soil

Abstract: BackgroundThe consecutive monoculture for most of medicinal plants, such as Rehmannia glutinosa, results in a significant reduction in the yield and quality. There is an urgent need to study for the sustainable development of Chinese herbaceous medicine.Methodology/Principal FindingsComparative metaproteomics of rhizosphere soil was developed and used to analyze the underlying mechanism of the consecutive monoculture problems of R. glutinosa. The 2D-gel patterns of protein spots for the soil samples showed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 64 publications
3
84
0
Order By: Relevance
“…In that study, microorganisms were sampled from leaf material, and parallel metagenomics and metaproteomics analyses were performed using one-dimensional protein separation followed by liquid chromatography high-accuracy mass spectrometry. Metaproteomic studies of rhizosphere samples are still at its beginning and first reports were only published very recently Wu et al, 2011). In those studies, proteins were directly extracted from rhizosphere samples (without a preceding physical enrichment step of microbial cells; Bastida et al, 2009), separated by twodimensional gel electrophoresis and identified by MALDI-TOF/TOF.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, microorganisms were sampled from leaf material, and parallel metagenomics and metaproteomics analyses were performed using one-dimensional protein separation followed by liquid chromatography high-accuracy mass spectrometry. Metaproteomic studies of rhizosphere samples are still at its beginning and first reports were only published very recently Wu et al, 2011). In those studies, proteins were directly extracted from rhizosphere samples (without a preceding physical enrichment step of microbial cells; Bastida et al, 2009), separated by twodimensional gel electrophoresis and identified by MALDI-TOF/TOF.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade environmental proteomics has broadened its analytical spectrum to various natural and polluted soil types, plant phyllosphere and rhizosphere, waters and other environmental matrices, such as organic wastes and mine spoils (Wilmes and Bond, 2004;Tyson et al, 2004;Ram et al, 2005;Schulze et al, 2005;Benndorf et al, 2007;Chourey et al, 2010;Williams et al, 2010;Wang et al, 2011;Wu et al, 2011). Early environmental proteomics aimed at developing efficient methods for increasing the yield of protein extraction in the direction 'the more the proteins the better', leading mostly to inventories of bulk soil proteins than to discovery of relevant protein expression profile of soil microbial communities.…”
Section: Advances In Environmental Proteomicsmentioning
confidence: 99%
“…The relative rarity of key function protein molecules against a background of abundant and diverse structural proteins may be responsible for the low rate of unique discoveries in soil metaproteomic studies, despite the rapid progress in protein extraction and detection methodologies. Even the most exhaustive studies are only able to identify 10e300 proteins (Benndorf et al, 2007;Chourey et al, 2010;Williams et al, 2010;Wang et al, 2011;Wu et al, 2011). Soil proteolytic activity (Renella et al, 2002) and geochemical denaturation are partially responsible for the low yield of protein extraction and identification.…”
Section: Genomes (Nbci)mentioning
confidence: 99%
“…Previous studies showed that rhizospheric microbial dynamics largely governed proper soil ecosystem function and had close interaction with consecutive monoculture problems (Qu and Wang, 2008;Qi et al, 2009;Wu et al, 2009;Wu et al, 2011;Li et al, 2012b;Wu et al, 2013). Crop consecutive monoculture not only alters the physical and chemical properties of the soil, but also contributes to the development of diverse microbial groups in the rhizosphere (Minh, 2005;Lin et al, 2007;Yoneyama and Natsume, 2010;Berendsen et al, 2012;Ndabamenye et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The autotoxic compounds were often isolated from consecutive monoculture soil, such as phenolic acid and aliphatic acid compounds, which could selectively enhance specific microbial populations in the soil which then leads to a shift in microbial communities (Qu and Wang, 2008;Li et al, 2012b). Wu et al (2011) analyzed the rhizospheric biological properties of consecutively monocultured R. glutinosa using soil metaproteomics and found that consecutive monoculture can induce the changes of microbes in the expression of proteins.…”
Section: Introductionmentioning
confidence: 99%